2021
DOI: 10.1617/s11527-021-01823-6
|View full text |Cite
|
Sign up to set email alerts
|

The direct shear behavior of recycled lump concrete

Abstract: To study the direct shear behavior of recycled lump concrete, 116 prismatic specimens were fabricated and tested under double-direct shear loading. Four variables were considered: the replacement ratio of recycled concrete lumps, the characteristic ratio of recycled concrete lumps (i.e., the characteristic size of lumps as divided by the lateral dimension of prism), the prisms' lateral dimension and the strength of fresh concrete matrix. A formula has been established, which adequately predicts the direct shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…At present, most of the scholars refer to the ordinary concrete proportion design specification for recycled aggregate concrete proportion design, and use orthogonal test to seek the optimal proportion [10][11][12]. However, when using orthogonal tests to seek the optimal proportion, the consideration of the interaction between factors will lead to a large amount of workload, and it is not possible to obtain a clear functional relationship between the factors and the response values in the specified area [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the scholars refer to the ordinary concrete proportion design specification for recycled aggregate concrete proportion design, and use orthogonal test to seek the optimal proportion [10][11][12]. However, when using orthogonal tests to seek the optimal proportion, the consideration of the interaction between factors will lead to a large amount of workload, and it is not possible to obtain a clear functional relationship between the factors and the response values in the specified area [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, concrete in practical engineering, such as corbels, highways, bearing padding stones, and deep beams, is usually subjected to combined compression-shear loads during service. [37][38][39][40] Then the study of RAC under complex stress state is very important. Deng et al 41 and Wang et al 42 performed the direct shear tests and the compressionshear tests on RAC and revealed a significant difference in the shear behavior between RAC under pure shear stress and combined compression-shear stresses.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, some researchers found that the drops in splitting tensile strength and flexural strength due to the substitution of NCA with RCA were to a large extent compensated by the addition of PP fibers. However, concrete in practical engineering, such as corbels, highways, bearing padding stones, and deep beams, is usually subjected to combined compression‐shear loads during service 37–40 . Then the study of RAC under complex stress state is very important.…”
Section: Introductionmentioning
confidence: 99%